2015
DOI: 10.7314/apjcp.2015.16.17.7871
|View full text |Cite
|
Sign up to set email alerts
|

Hepatic Resection after Initial Transarterial Chemoembolization Versus Transarterial Chemoembolization Alone for the Treatment of Hepatocellular Carcinoma: A Meta-analysis of Observational Studies

Abstract: Background: There is no consensus regarding the selection of treatment options for hepatocellular carcinoma (HCC) after initial transarterial chemoembolization (TACE). This meta-analysis aimed to explore the survival benefit of hepatic resection after initial TACE for the treatment of HCC. Materials and Methods: We searched three major databases to identify all relevant papers comparing the outcomes of hepatic resection after initial TACE versus TACE alone for the treatment of HCC. Hazard ratios (HRs) with 95%… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 22 publications
1
5
0
Order By: Relevance
“…Consistent with previously studies, our analysis demonstrates that an add‐on resection or ablation after initial TACE significantly extended the survival time and increased the percentage of patients who reached a 3‐year survival time . This suggests that add‐on resection/ablation works synergistically with TACE.…”
Section: Discussionsupporting
confidence: 90%
“…Consistent with previously studies, our analysis demonstrates that an add‐on resection or ablation after initial TACE significantly extended the survival time and increased the percentage of patients who reached a 3‐year survival time . This suggests that add‐on resection/ablation works synergistically with TACE.…”
Section: Discussionsupporting
confidence: 90%
“…This may offset the relatively shorter PFS resulting from the W-W strategy. Previous studies have reported a significantly improved OS in patients who underwent hepatic resection after initial TACE compared to those who received TACE alone 28 . However, these studies aimed to investigate the survival benefits of hepatic resection following TACE for the treatment of HCC.…”
Section: Discussionmentioning
confidence: 95%
“…According to the BCLC stage system, TACE is the standard therapy for BCLC stage B (intermediate HCC) patients and plays an important role in replacing other therapies that are not applicable regarding early or advanced HCC[ 31 ]. Many meta-analyses have demonstrated that pre-operative TACE has no significant effect on improving the survival of patients with resectable HCC[ 32 - 34 ], but none of them mentioned the effect on unresectable HCC.…”
Section: Resultsmentioning
confidence: 99%